Kinetic studies on the cleavage of adenovirus DNA by restriction endonuclease Eco RI. - Forsblom, S (1976)
The kinetics of cleavage of DNA from Adenovirus Type 1 (Ad1), Type 5 (Ad5) and Type 6 (Ad6) by restriction endonuclease EcoRI was investigated by quantitative evaluation of the fluorescence from ethidium stained DNA fragments separated on agarose gels. The apparent rate constants of cleavage at different cleavage sites have been determined and large differences in the cleavage rates of the individual sites within one type of DNA were found. From the kinetics of cleavage information on the sequence of the DNA fragments can be obtained. The order of the fragment A, B, C, D of Ad6 DNA obtained after complete cleavage by restriction endonuclease Eco RI was found to be A-D-C-B; the order of the corresponding fragments A, B, C of Ad1 and Ad5 DNA was found to be A-C-B.